PENINGKATAN HASIL BELAJAR PKn DENGAN PENDEKATAN KOOPERATIF MODEL THINK PAIR SHARE (TPS) DI SEKOLAH DASAR - Marhevi, Marhevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The problem found at the Fourth Grade of SDN 10 Parit Batu that students’ achivement in learning Civics was low. The aim of the research is to describe improving students’ acchievement in learning civics by using the cooperative approach models think pair share (TPS) at the fourth grade of SDN 10 Parit Batu, Tigo Nagari. The data collected used in this study was a qualitative and quantitative and the method was classroom action research. Based on the research it can be seen that the overall of first cycle was 68% and the second cycle results was 80%. It can be summarized, students’ achivement in learning civic can be improved by using Think Pair Share (TPS at the Fourth grade students of SDN 10 Parit batu. Kata Kunci: hasil belajar; pkn; model tps